Long-term clinical effectiveness of continuous positive airway pressure therapy versus non-invasive ventilation therapy in patients with obesity hypoventilation syndrome: a multicentre, open-label, randomised controlled trial. Issue 10182 (27th April 2019) - Masa, Juan F; Mokhlesi, Babak; Benítez, Iván; Gomez de Terreros, Francisco Javier; Sánchez-Quiroga, Maria Ángeles; Romero, Auxiliadora; Caballero-Eraso, Candela; Terán-Santos, Joaquin; Alonso-Álvarez, Maria Luz; Troncoso, Maria F; González, Mónica; López-Martín, Soledad; et al.
Summary: Background: Obesity hypoventilation syndrome is commonly treated with continuous positive airway pressure or non-invasive ventilation during sleep. Non-invasive ventilation is more complex and costly than continuous positive airway pressure but might be advantageous because it provides ventilatory support. To date there have been no long-term trials comparing these treatment modalities. We therefore aimed to determine the long-term comparative effectiveness of both treatment modalities. Methods: We did a multicentre, open-label, randomised controlled trial at 16 clinical sites in Spain. We included patients aged 15–80 years with untreated obesity hypoventilation syndrome and an apnoea-hypopnoea index of 30 or more events per h. We randomly assigned patients, using simple randomisation through an electronic database, to receive treatment with either non-invasive ventilation or continuous positive airway pressure. Both investigators and patients were aware of the treatment allocation. The research team was not involved in deciding hospital treatment, duration of treatment in the hospital, and adjustment of medications, as well as adjudicating cardiovascular events or cause of mortality. Treating clinicians from the routine care team were not aware of the treatment allocation. The primary outcome was the number of hospitalisation days per year. The analysis was done according to the intention-to-treat principle. This study is registered withClinicalTrials.gov, numberNCT01405976 . Findings: From May 4, 2009, to March 25, 2013, 100 patients were randomly assigned to the non-invasive ventilation group and 115 to the continuous positive airway pressure group, of which 97 patients in the non-invasive ventilation group and 107 in the continuous positive airway pressure group were included in the analysis. The median follow-up was 5·44 years (IQR 4·45–6·37) for all patients, 5·37 years (4·36–6·32) in the continuous positive airway pressure group, and 5·55 years (4·53–6·50) in the non-invasive ventilation group. The mean hospitalisation days per patient-year were 1·63 (SD 3·74) in the continuous positive airway pressure group and 1·44 (3·07) in the non-invasive ventilation group (adjusted rate ratio 0·78, 95% CI 0·34–1·77; p=0·561). Adverse events were similar between both groups. Interpretation: In stable patients with obesity hypoventilation syndrome and severe obstructive sleep apnoea, non-invasive ventilation and continuous positive airway pressure have similar long-term effectiveness. Given that continuous positive airway pressure has lower complexity and cost, continuous positive airway pressure might be the preferred first-line positive airway pressure treatment modality until more studies become available. Funding: Instituto de Salud Carlos III, Spanish Respiratory Foundation, and Air Liquide Spain.